Experimental study of liquid metal heat transfer in a vertical duct affected by coplanar magnetic field: Upward flow. (August 2020) - Razuvanov, Nikita; Pyatnitskaya, Natalya; Frick, Peter; Belyaev, Ivan; Sviridov, Valentin
Highlights: Liquid metal heat transfer in symmetrically and asymmetrically heated duct with upflow is considered. Significant heat transfer enhancement by thermogravitation is found for one-sided heated duct. Heat transfer is slightly dependent to magnetic field imposition. Flow regularities continue to change by the whole length of the studied duct when the magnetic field is applied. Abstract: Liquid metal cooling is of interest in high heat load applications. Convection of liquid metals in mass force fields, i.e., buoyancy, inertia, magnetic fields, is a problem which is still difficult to predict due to lack of experimental data. There is a special interest in the heat removal systems of a tokamak reactor, where high heat and magnetic fields form unprecedented conditions. Continuing the study of heat transfer in channels with a liquid metal coolant, we consider the upward flow of mercury in a vertical heated rectangular duct located in a strong magnetic field. Specifically, we study experimentally the mercury flow under a coplanar magnetic field (directed transverse to the main flow and along the long side of the duct) for symmetrical (two-sided) and asymmetrical (one-sided) duct heating. The upward flow configuration has enabled us to explore experimentally flow development along the duct using a 3D probe temperature measurement scanning technique. As in the downward flow configuration, the joint action of buoyancy and magnetic forces result in a drastic peculiarity of heat transfer regimes, where buoyancy and magnetic influence can not be neglected. We show that, in contrast to the downward flow, buoyancy effects play a primary role in flow and heat transfer.